Front cover: Milk Polar Lipids in a High‐Fat Diet Can Prevent Body Weight Gain: Modulated Abundance of Gut Bacteria in Relation with Fecal Loss of Specific Fatty Acids. Issue 4 (18th February 2019) - Milard, Marine; Laugerette, Fabienne; Durand, Annie; Buisson, Charline; Meugnier, Emmanuelle; Loizon, Emmanuelle; Louche‐Pelissier, Corinne; Sauvinet, Valérie; Garnier, Lorna; Viel, Sébastien; Bertrand, Karène; Joffre, Florent; et al.
Abstract : Mol. Nutr. Food Res. 2019, 63, 1801078 DOI:10.1002/mnfr.201801078 Polar lipids of the milk fat globule membrane are an emerging functional ingredient. In article number1801078, Marie‐Caroline Michalski and co‐workers show in mice that when added to a high‐fat diet, 1.6% of milk polar lipids reduces body weight gain, modulates the abundance of bacteria of metabolic interest in the gut microbiota, and impacts colon morphology. Unabsorbed residues from milk sphingomyelin could explain these effects.